THE INFLUENCE OF ENTREPRENEURIAL GRIT, COGNITIVE FLEXIBILITY, DIGITAL PAYMENT ADOPTION, AND INFORMAL NETWORKING ON MSME GROWTH IN INDONESIA - Adnan, Ahmad Zaelani; Zukfikri, Agung (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the influence of entrepreneurial grit, cognitive flexibility, digital payment adoption, and informal networking on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a quantitative research design and structural equation modeling (SEM) with data collected from 312 MSME owners across Java Island, the study finds that all four variables have a positive and significant effect on MSME growth. Entrepreneurial grit and cognitive flexibility represent internal psychological capacities that enable entrepreneurs to persist and adapt amid challenges, while digital payment adoption and informal networking reflect external and relational resources that facilitate operational efficiency and market access. The results show that these combined factors explain 52.9% of the variance in MSME growth. The findings suggest that strengthening both internal capabilities and external linkages is essential for promoting MSME development. Practical implications are discussed for entrepreneurship training programs, digital transformation strategies, and community-based support mechanisms.